Risk assessment of selected wastewater treatment plant in Klang Valley / Ooi Chin Hui - Oii, Chin Hui (2018)
Since the industrial revolution at 18th century, the industrial activities increased considerably and the wastewater is discharged to the nearby river without treatment, which lead to disease outbreak. People start aware on the need of wastewater treatment for the sake of environment and human health, and it became a compulsory to treat the wastewater before discharge to the environment. However, while operating the wastewater treatment plant, there will be risk associated in the operation, which categorized into 3 main types: physical, health and environmental risk. Therefore, risk assessment is used in order to understand the risk, and to develop control action in dealing with the risk. It is carried out in a selected premise in Klang Valley which including safety checklist, qualitative risk assessment, operators’ survey and cleaner production assessment. According to the checklist, the manual handling and the waste management in the premise are poor which is high possible to cause risk to the operators and the environment. While from the qualitative risk assessment, the high risk hazards are identified which required extra attention to control the risk. From the operators’ survey, it is found out that the operators are poor in competency / knowledge in safe operation, emergency preparation and response, and contribution to continual safety improvement. Risk control is required to minimize the risk identified and to improve the safety level in the premise by elimination, substitution, engineering control, administrative control and personal protective equipment (PPE). Cleaner production assessment is carried out to assess the possibility to reduce the resource usage and the waste production hence lead to cost saving, from the assessment in the selected premise, the resource can be reduced by reuse treated water instead of paying bill for clean water usage, and use more energy saving electric starter: variable frequency drive (VFD). The dried sludge produced by the premise content rich in nutrient value to be resell as organic fertilizer to bring profit to the premise instead of direct disposal.